Tuesday

September 16, 2014

September 16, 2014

Posted by **Elizabeth** on Thursday, April 18, 2013 at 10:20pm.

n^2-2n+1=5

- Algebra -
**DW**, Thursday, April 18, 2013 at 10:38pmn^2-2n-4=0

a=1 b=-2 c=-4

then use quadratic formula

x=(-b+sqrt(b^2-4ac))/(2a)

x=(-b-sqrt(b^2-4ac))/(2a)

x=1+sqrt(5)

x=1-sqrt(5)

**Answer this Question**

**Related Questions**

math - Solve each equation and leave the answer in simplest radical form. x ...

trigonometry - Complete the square to Solve Quadratic Equation: Solve the ...

trigonometry - Complete the square to Solve Quadratic Equation: Solve the ...

Math-Involing i's - 1)What is the product of 5+ Radical (-36) and 1-Radical (-49...

maht,correction - Find the area of the rectangle shown in the figure. length = ...

MATH - solve 1-(2/x)=2/(x+2) Express your answer in simplest radical form. What ...

math - What is the perimeter of a right triangle with legs 6 cm and 3 cm? Leave ...

algebra - Solve using the quadratic formula and leave the answer in radical form...

Math - what is the perimeter of a right triangle with legs 6 cm and 3cm , leave...

algebra - 1.what is the simplest form of the producy sqrt 50x^7y^7 * sqrt 6 xy^4...